Consumption Smoothing after the Final Mortgage Payment: Testing the Magnitude Hypothesis - Scholnick, Barry (The Review of Economics and Statistics, 2013)
We examine whether the magnitude of an anticipated income change affects consumption smoothing (the magnitude hypothesis). Although this hypothesis has been discussed for fifty years, we are one of the first to provide formal statistical evidence to support it. We consider the natural experiment of an individual's final mortgage payment, an anticipated income change, and examine how it affects credit card expenditure. We can identify causality because the dates of final mortgage payments across individuals are uncorrelated with unobserved determinants of consumption. Using an event study methodology, we provide evidence to support the magnitude hypothesis.